Analisis Kesiapan Mahasiswa Kearsipan dalam Memasuki Dunia Kerja: Pengaruh Pendidikan, Pengalaman Praktikum, dan Motivasi - Kurniatun, Kurniatun; Eﬀendi, Ully Isnaeni; Santosa, Heri (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
The work readiness of graduates of the archival study program is an important concern in responding to the challenges of an increasingly competitive world of work. Students' readiness to enter the workforce must be prepared from the educational stage. This study aims to analyze the factors inﬂuencing archival students' readiness for the professional world. This study uses an associative quantitative research design, and applies a survey method with a Likert scale questionnaire in data collection. The sample was determined using a simple random sampling technique. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that archival education, internship experience, and work motivation play a role in students' readiness to work in the archival ﬁeld. Work motivation has a signiﬁcant impact on job readiness, while archival education not only signiﬁcantly aﬀects job readiness but also inﬂuences work motivation. In contrast, internship experience does not have a direct signiﬁcant effect on job readiness but signiﬁcantly contributes to increasing work motivation in the archival ﬁeld.